William Shakespeare’ın Hamlet Yapıtının A. J. Greimas’ın Eyleyensel Örnekçesine Göre Çözümlenmesi - Baloğlu, Uğur (The Turkish Online Journal of Design, Art and Communication, 2013)
The analysis of semiology has been previously used in only linguistic analysis but in time it was started to be used to analyse in different ares such as cinema, music, advertising poster etc. In this article, Algirdas Julien Greimas’s the actantial model and narrative curriculum will be discussed who was inspired by narrative science of Vladimir Propp in respect to the structuralism and making up his own analysis method. Considering these facts, William Shakespeare’s play ‘Hamlet’ adaptation is going to be analyzed according to A.J. Greimas’s actantial model.
Keywords: William Shakespeare; Hamlet; Greimas